Evaluating human perceptions of android robot facial expressions based on variations in instruction styles - Fujii, Ayaka; Ishi, Carlos Toshinori; Sakai, Kurima; Funayama, Tomo; Iwai, Ritsuko; Takahashi, Yusuke; Kumada, Takatsune; Minato, Takashi (Frontiers in Robotics and AI, 2025)
Robots that interact with humans are required to express emotions in ways that are appropriate to the context. While most prior research has focused primarily on basic emotions, real-life interactions demand more nuanced expressions. In this study, we extended the expressive capabilities of the android robot Nikola by implementing 63 facial expressions, covering not only complex emotions and physical conditions, but also differences in intensity. At Expo 2025 in Japan, more than 600 participants interacted with Nikola by describing situations in which they wanted the robot to perform facial expressions. The robot inferred emotions using a large language model and performed corresponding facial expressions. Questionnaire responses revealed that participants rated the robot’s behavior as more appropriate and emotionally expressive when their instructions were abstract, compared to when they explicitly included emotions or physical states. This suggests that abstract instructions enhance perceived agency in the robot. We also investigated and discussed how impressions towards the robot varied depending on the expressions it performed and the personality traits of participants. This study contributes to the research field of human–robot interaction by demonstrating how adaptive facial expressions, in association with instruction styles, are linked to shaping human perceptions of social robots.